2022
DOI: 10.34172/jrcm.2022.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and its effect on serum vitamin D and iron among adult female: A review from Middle East perspective

Abstract: Hypothyroidism is a pathophysiological phase in which insufficient hormones are produced leading to an imbalance in basal metabolic rate and inefficiency physiological role of body systems. Vitamin D affects thyrocytes by decreasing TSH stimulated iodide uptake and cellular development. In hypothyroidism, hypovitaminosis D are due to malabsorption from the intestine and the other mechanism is inactivation of vitamin D. Thyroid hormones induce erythropoietin gene expression causing increase secretion of erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…11,19,20 Following, a review study indicated that thyroid hormones activate erythropoietin gene expression, leading to an increase in erythropoietin secretion and reduced thyroid peroxidase enzyme activity an iron dependent crucial enzyme involved in thyroid hormone production. 21 Menorrhagia and microcytic anaemia can result from hypothyroidism due to iron malabsorption. 2 Thus, iron is an important factor that should be taken in account while treating hypothyroid individuals and also measuring the iron profile in hypothyroid individuals may be beneficial, as iron shortage may be the underlying reason.…”
Section: Discussionmentioning
confidence: 99%
“…11,19,20 Following, a review study indicated that thyroid hormones activate erythropoietin gene expression, leading to an increase in erythropoietin secretion and reduced thyroid peroxidase enzyme activity an iron dependent crucial enzyme involved in thyroid hormone production. 21 Menorrhagia and microcytic anaemia can result from hypothyroidism due to iron malabsorption. 2 Thus, iron is an important factor that should be taken in account while treating hypothyroid individuals and also measuring the iron profile in hypothyroid individuals may be beneficial, as iron shortage may be the underlying reason.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid diseases are one of the most common endocrine disorders in the world ( 1 ), affecting approximately 40% of the world’s population ( 2 ). Thyroid hormones, including triiodothyronine (T 3 ) and thyroxine (T 4 ), have prominent effects on human metabolism, growth, and development.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous thyroid disorders. Hypothyroidism is a pathophysiological phase with insufficient hormone production, resulting in an imbalance in basal metabolic rate and inefficient physiological roles of the body systems ( 1 ). Hypothyroidism might be clinical/overt, with an elevation in the thyroid-stimulating-hormone (TSH) and low levels of free T 4 (fT 4 ), or subclinical, with normal levels of fT 4 and elevated serum TSH ( 5 ).…”
Section: Introductionmentioning
confidence: 99%